EKSISTENSI OTORITAS JASA KEUANGAN DALAM PENGAWASAN TERHADAP USAHA PERGADAIAN DI INDONESIA - Lingga Nadhira Adevia Putri; Inaya Aulia Mizan; Indryana Widi Ardhianty; Dzulfiqar Prakoso Nursukma (Universitas Negeri Semarang, 2024)
Digital transformation has become a major driver in increasing efficiency, accessibility and innovation in the national economic system. However, in practice, many legal discrepancies occur. This is caused by the rise of financial institutions that operate without complying with applicable legal provisions. The government created the Otoritas Jasa Keuangan (OJK) in response to the need for a more orderly and effective financial system to improve the Indonesian economy. OJK is an independent institution responsible for the supervision and regulation of the financial industry. One of OJK's important functions is to ensure that standards and regulations apply in the supervision of non-bank financial organizations such as pawnshops. Pegadaian, as a financial institution operating in Indonesia, is subject to supervision and regulations set by the OJK. Peraturan Otoritas Jasa Keuangan (POJK) Nomor 31/POJK.05/2016 is the main instrument that regulates various aspects of pawnshop operations and business activities in Indonesia. This article discusses the regulation of pawnshop businesses in PJOK and how the existence of OJK is related to its supervision of pawnshop businesses. This writing uses a normative juridical writing method. It includes primary and secondary legal materials.. The conclusion of this article is that the existence of the OJK and its role in supervising pawnshop businesses is crucial in maintaining the integrity and security of the financial sector in Indonesia. OJK efforts to improve the quality of supervision and regulation can also help overall economic growth.